Perancangan Model Bisnis Ayam Petelur BUMDes Curugbitung Menggunakan Kerangka Kerja Bisinis Model Canvas - Muh Faturokhman; Aceng Hidayat; Warcito Warcito; Liisa Firhani Rahmasari; Mokhamad Syaefudin Andrianto (Jurnal Pusat Inovasi Masyarakat, 2026)
The failure of Village-Owned Enterprises (BUMDes) is often caused by limited business concepts and difficulties in explaining the concepts to stakeholders. BUMDes Curugbitung has several business plans that have not been optimally implemented. One reason is the lack of business plans that are easily communicated to various parties. The DOSEN PULANG KAMPUNG Program aims to help BUMDes conduct systematic business planning to anticipate business failures and attract investors. The mentoring method uses a participatory workshop with a Business Model Canvas (BMC) framework. This workshop was held July 7, 2025, and involved 20 participants, consisting of BUMDes administrators and Gapoktan (Farmer Groups), while lecturers and students acted as facilitators. The workshop outlined nine key building blocks egg-laying chicken business for the Curugbitung BUMDes. Participants, particularly BUMDes administrators and farmer groups (Gapoktan), gained a more comprehensive understanding of business planning. The BMC model assisted BUMDes managers in explaining strategies to stakeholders. Managerial knowledge, including marketing, production, finance, and human resources, determines the success of BMC implementation. BUMDes managers also require a shift in mindset and institutional strengthening. The results of this business model are expected to provide discussion material for BUMDes managers in seeking funding sources and sustainable business.